Fabrication of stircast ZA/ZrB2 reinforced in-situ composites - Kumar V.; Mishra A.; Mohan S.; Mohan A. (My University, 2025)
This work outlines the preparation of Zinc-Aluminium (ZA)/ZrB2 composite via in situ stir casting technique. X-ray diffractometer (XRD) has been used for phase identification, optical microscopy (OM) for microstructural analysis and scanning electron microscopy (SEM) for in-depth analysis of microstructure. Four compositions with 0, 3, 6 and 9 vol% ZrB2 were prepared. XRD analysis confirms the formation of ZrB2 particles. It also shows peaks of zinc and aluminium. Absence of any other peak confirms that reaction was completed. Optical micrographs show that generation of second phase particles has refined the grains of matrix phase. Hexagonal and rectangular morphology of particles is clearly observed while studying under SEM. Evaluation of mechanical properties shows that with increase in ZrB2 vol% the tensile strength as well as compressive strength increases at the expense of ductility. Also remarkable increase in hardness is measured with increase in ZrB2 vol%. © 2019 IOP Publishing Ltd.